IMPLEMENTASI PELATIHAN PEMBUATAN WEBSITE UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL SISWA SMKS BINTANG NUSANTARA - Norita Sinaga; Sutrisno; Rajin Nahampun (Abdi Jurnal Publikasi, 2025)
This community service activity aims to analyze the effectiveness of website development training in improving the professional competence of SMK Bintang Nusantara students. Rapidly evolving digital technology demands that SMK graduates possess skills relevant to industry needs, particularly in web development. The method used in this activity was training and implementation, encompassing learning HTML, CSS, JavaScript, and modern frameworks, using a hands-on approach. Participants in the community service activity consisted of 23 11th-grade students majoring in Computer and Network Engineering at SMKS Bintang Nusantara. The analysis of the activity showed that the students began to understand how to create an independent portfolio and store it in a GitHub repository. The conclusions of this community service activity indicate that the website development training significantly improved the technical competence and improvisation of SMKS Bintang Nusantara students. Suggestions include integrating similar training into the regular curriculum and expanding the scope of material to include more advanced and up-to-date website technologies.